DESENTRALISASI PENGELUARAN DI INDONESIA - Siti Herni Rochana (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2013)
Since the implementation of Law 22/1999 and Law 25/1999 of 2001, has been an increase in the implementation of fiscal decentralization with a phenomenon called Big Bang. The study was conducted to determine the degree of decentralization of expenditure covering the period before and after the implementation of regional autonomy. The research data is a panel data drawn from 30 provinces between 1994 to 2007. The results showed that in Indonesia there has been a significant increase in expenditure decentralization since 2001. Significant increases occurred mainly on the expenditure side, especially the decentralization of authority be spending more than doubled from the previous. On a national scale, the degree of decentralization of authority expenditure increased from 10.48% in the year 2000 to 25.45% in 2001. And the average for each province, the degree of decentralization of spending authority increased from 0.40% in 2000 to 0, 85% in 2001DOI: 10.15408/sjie.v2i2.2423